Battery-Supercapacitor Energy Storage - Hadarz, Martin; Julander, Martin (My University, 2008)
In the strive to further improve the lifetime and performance of a hybrid vehicle drivetrain, one of the most challenging task is to increase the electrical power and energy storage. The process of storing electric energy chemically in batteries is afflicted both with losses, power limitations and limited usage. By introducing a supercapacitor as aid to increase system power and mitigate the battery from stresses, the performance of the combined energy storage unit is improved. To evaluate the increased performance, a DC/DC converter was constructed and evaluated to verify the simulations and improve the understanding of the system. Simulations in Matlab® Simulink® were conducted to investigate the mitigation of battery stresses with different control strategies and system setups. The efficiency and power of the energy storage unit was improved, and it is clearly shown that the battery stresses are reduced when a supercapacitor is introduced.
Keywords: Elkraftteknik; Electric power engineering